2017
DOI: 10.12659/msm.907364
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Adjacent Vertebral Compression Fracture Following Percutaneous Vertebroplasty After Menopause: A Retrospective Study

Abstract: BackgroundClinically, percutaneous vertebroplasty (PVP) is frequently applied to treat osteoporotic vertebral compression fracture (OVCF). It is believed that new compression fractures are more likely to occur adjacent to the PVP-treated segment, typically within 1 month after PVP. The purpose of this study was to investigate risk factors for adjacent vertebral compression fractures (AVCF) after PVP in patients with OVCF after menopause.Material/MethodsBetween Jun 2012 and Dec 2016, 412 patients were initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…The most common type of osteoporotic fracture is OVCF, affecting nearly 25% of the elderly population who are older than 50 years. 1,25 OVCF raises the risk for new vertebral fractures 5fold in the first year, and the presence of two or more OVCFs increases the risk up to 12-fold. 26 The number of subsequent fractures is associated with increased mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…The most common type of osteoporotic fracture is OVCF, affecting nearly 25% of the elderly population who are older than 50 years. 1,25 OVCF raises the risk for new vertebral fractures 5fold in the first year, and the presence of two or more OVCFs increases the risk up to 12-fold. 26 The number of subsequent fractures is associated with increased mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Whether kyphoplasty increases the fracture rate of adjacent vertebral bodies after surgery remains controversial. Li et al 20 reported that high levels of bone density can protect adjacent vertebral bodies from fractures after surgery. Ahn et al 21 found that differences in vertebral body strength caused by bone cement augmentation resulted in fractures of adjacent vertebral bodies, while the difference in segmental mobility caused fractures of non-adjacent vertebral bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. 20 reported that high levels of bone density can protect adjacent vertebral bodies from fractures after surgery. Ahn et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is some controversy among authors regarding a possible relationship between the realization of PVP and the appearance over time of new FV [31][32][33] . This reason justifies the analysis, such as the one we present here, where post-surgery follow-ups are recorded much longer over time.…”
Section: Originalsmentioning
confidence: 99%